Food Security and the Dynamics of Wheat and Maize Value Chains in Africa and Asia - Grote, Ulrike; Fasse, Anja; Nguyen, Trung Thanh; Erenstein, Olaf (Frontiers in Sustainable Food Systems, 2021)
There is an ongoing debate about how best to feed the growing world population in the long run and associated implications for research and development. Some call for a new Green Revolution to secure the supply of staple foods, whereas others emphasize the importance of diversifying and improving people's diets. We aim to contribute to this debate by reviewing the case of wheat and maize value chains and their contribution to food security in Africa and Asia. We first identify drivers transforming food systems. We then apply these to the cereal value chains and disentangle their effects on food security. We thereby add to the three strands in the literature around production, consumption, and food system transformation and point to different research needs and recommendations for the future. The review highlights: (1) Wheat and maize production will be increasingly impaired by ecological drivers such as land degradation, water scarcity and climate change. (2) There are promising innovations to increase and maintain productivity, but constraints in adopting these innovations have to be overcome (i.e., access to seeds, finance, and education/training). (3) The drivers affect all four dimensions of food security, but first and foremost they determine the availability and stability of maize and wheat. This indirectly also influences the economic and physical access of people to maize and wheat. (4) Research tends to focus on improving the productivity and sustainability of wheat and maize farming which is largely interlinked with the availability dimension of food security. (5) The stability and utilization dimension of food security merits continued yet increased support. First, to address climate change and implications for biotic and abiotic stresses. Second, to promote healthier diets and enable the equitable transformation of food systems.